Pausa para tu Salud: Reduction of Weight and Waistlines by Integrating Exercise Breaks into Workplace Organizational Routine - Agustin Lara, MD, SPH; Antronette K. Yancey, MD, MPH; Roberto Tapia-Conyer, MD, MPH, MSc, DrSc; Yvonne Flores, PhD; Pablo Kuri-Morales, MD, MSc, SPH; Ritesh Mistry, PhD; Elena Subirats, MPH; William J. McCarthy, PhD (Centers for Disease Control and Prevention, 2008)
IntroductionProactive worksite strategies that change the physical or sociocultural environment(s) to incorporate obligatory physical activity may be necessary to engage sedentary people. This study describes implementation and evaluation of an intervention, Pausa para tu Salud (Pause for Your Health), that integrated a brief period of group exercise into the workday.MethodsAn uncontrolled pretest-post-test study design tested the effects of integrating daily 10-minute exercise breaks during paid work time during January 2003 through January 2004. A total of 335 Mexican Ministry of Health office workers provided baseline data as a part of routine annual clinical screening examinations.ResultsBaseline mean body mass index and waist circumferences were 27.8 kg/m2 and 87.6 cm for women and 26.6 kg/m2 and 89.7 cm for men. Complete data were available for 271 (80.9%) employees at 1-year follow-up. Two-tailed, paired t-test comparisons were used. Body mass index decreased by 0.32 kg/m2 (P = .05), and waist circumference by 1.6 cm (P = .0009) overall. The body mass index decrease, however, was significant only for men (−0.43 kg/m2, P = .03). Multivariate analyses revealed a significant decrease in diastolic blood pressure among women (z = −2.04, P = .042).ConclusionThe intervention was associated with significant improvements in both measures of body composition. Substantive health and organizational benefits may result from integrating brief periods of physical activity into the workday if these findings are replicated in randomized controlled trials in other worksites.